Kesiapsiagaan Sekolah Dalam MenghadapiBencana Gempabumi di SMA Negeri 1 WediKabupaten Klaten - Faedah, Solpin (2016)
Solpin Faedah / A610100047 SCHOOL IN DEALING WITH DISASTER PREPAREDNESS EARTHQUAKE IN SMA NEGERI 1 WEDI DISTRICT KLATEN Study Program of Geography, Faculty of Teacher Training and Education University Muhammadiyah of Surakarta, 2016 SMA Negeri 1 Wedi is located in the district of Klaten is one of the areas affected by the earthquake with the death toll is quite a lot. The earthquake that occurred on 27 May 2006 also resulted in the destruction of residential areas (BPBD Klaten). SMA Negeri 1 Wedi is one of the many schools damaged by the earthquake which occurred on May 27, 2006. This earthquake resulted in the school building cracked. I need to know from this study is the level of preparedness in the face of the earthquake disaster. This study aims to identify the earthquake disaster preparedness in SMA Negeri 1 Wedi. This study used survey method. The data collection method using random sampling methods were conducted on teachers and students. Moderate method of analysis used descriptive quantitative. Collecting data using questionnaires and structured interviews are also used as a technique of data pegumpulan, when researchers or data collectors have been know for sure about the information to be obtained. Results of research conducted in SMA Negeri 1 Wedi included in the category are almost ready with the acquisition of 61,38% index value. School component gained 61,96% index score in the category is almost ready, evidenced by the equipment that can capture information about the earthquake disaster warning and also their access to education through a simulated earthquake disaster preparedness. teacher preparedness index 60,18% categorized almost ready, the teacher SMA Negeri 1 Wedi know what to do in case of an earthquake, while the index of 66,34% in the category of student preparedness ready. Students never get knowledge about disaster warning, first aid, rescue and evacuation.